Current possibilities in the diagnosis of intrathoracic lymph node tuberculosis in children - A. A. Starshinova; I. F. Dovgalyuk; N. V. Korneva; S. M. Ananyev; P. V. Gavrilov; O. A. Yakunova (Туберкулез и болезни лёгких)
Diagnosing tuberculosis in children is very difficult. There are no clear diagnostic criteria for intrathoracic lymph node (ITLN) tuberculosis, the most common form of tuberculosis in children (78%). Current immunological methods used in combination with computed tomography make it possible to characterize a child’s status more clearly and to establish a correct diagnosis. The positive results of immunological tests in the presence of Mycobacterium tuberculosis infection require a set of radiological examination. ITLN tuberculosis is characterized by the fact that one group or more contains single or multiple ITLNs that measure more than 5 cm and differ in structure and density in the presence of positive immunological tests (Diaskintest and QuantiFERON test).